Film censorship in Malaysia: sanctions of religious, cultural and moral values - Wan Amizah WM,; Chang, Peng Kee; Jamaluddin Aziz, (2009)
Malaysia is one of the countries in the world that practices film censorship. The prevailing film censorship laws in Malaysia not only deal with all imported films, trailers and documentaries, but they also encompass the production and exhibition of local Malay films. A Film Censorship Board was established to censor or ban films infringing any religious, cultural and moral values of the Malaysian society, prior to public viewing. This paper outlines the evolution of film censorship in Malaya/Malaysia and discusses examples of several Malay films censored or banned on the grounds contradictory to religious, cultural and moral values set by the Board.